The Process Behind the Creation of a Framework for Participatory Game Design to Support Bilingual Education of Deaf Children - Galvão, Ludmilla Fernandes Oliveira; García, Laura Sánchez; Felipe, Tanya Amara; Honorato, Elaine Costa; Filho, José Cezar de Souza; Barbosa, Candida Vieira; Araújo, Kael Rhuan Campos de (Journal of the Brazilian Computer Society, 2026)
The deaf community needs computational tools that support Bilingual Education, which promotes the teaching of Libras (Brazilian Sign Language) as the first language and Portuguese as the second language from early childhood. Within this approach, the main objectives are to strengthen deaf identity and to foster bilingual competence. Although educational games can contribute to this process, many existing titles lack accessibility and fail to reflect the lived experiences of deaf children or the core principles of Bilingual Education. This issue arises because many games are created by developers unfamiliar with the needs of deaf children, underscoring the need for a tool to bridge this gap and include both teachers and deaf children in the game design process. To address this, we present the process behind the creation of the CAJEDUS-DP framework, aimed at facilitating the participatory specification of games to support Bilingual Education for deaf children. The framework promotes equal participation among game developers, deaf children, and their teachers, coordinated by a game producer. CAJEDUS-DP was designed using a methodology based on action research and participatory design during workshops with deaf children and teachers from the National Institute of Education for the Deaf (INES) and virtual meetings with indie game developers. This process revealed the potential for personal development of the participants, especially their creativity, self-confidence, and empathy. Moreover, it led to a game prototype aligned with the realities of deaf children and the objectives of Bilingual Education, named “Casa dos Bichos” (Animal Home). Last but not least, the CAJEDUS-DP framework provides a set of guidelines to assist in mediating the diverse partners involved in game design.